1999
DOI: 10.4039/ent13165-1
|View full text |Cite
|
Sign up to set email alerts
|

DIFFERENTIAL MORTALITY BETWEEN MALE AND FEMALE CHORISTONEURA OCCIDENTALIS (LEPIDOPTERA: TORTRICIDAE) LARVAE EXPOSED TO A BACULOVIRUS WITH OR WITHOUT OPTICAL BRIGHTENERS

Abstract: The Canadian Entomologist 131: 65 -70 (1999) Fifth-instar larval mortality was compared between male and female Choristoneura occidentalis Freeman exposed in the laboratory to sublethal doses of Choristoneura furniferana (Clem.) multicapsid nuclear polyhedrosis virus (CWNPV) with or without optical brighteners. More females than males died when the virus was used alone, but differences were not significant. When 1% brightener was added to CWNPV suspension, differences in larval mortality between males and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Subsequently, each caterpillar received an NPV‐treated or distilled water‐treated 5 mm diameter leaf disk (or artificial diet disk) of the same type they had been reared on following the methods of Li and Otvos, Raymond et al . and Wan et al .…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, each caterpillar received an NPV‐treated or distilled water‐treated 5 mm diameter leaf disk (or artificial diet disk) of the same type they had been reared on following the methods of Li and Otvos, Raymond et al . and Wan et al .…”
Section: Methodsmentioning
confidence: 99%
“…This suggested that more female larvae and/or pupae than males had died after larvae were treated by the virus. In a previous study, Li and Otvos (1999) found that female larvae of C. occidentalis were more susceptible to NPV than males. The alteration of sex ratio in favor of males has also been reported for other species by different researchers (Vargas-Osuna and Santiago-Alvarez 1988, Scheepens and Wysoki 1989, Duan and Otvos 2001.…”
Section: Discussionmentioning
confidence: 98%
“…Apart from protandry, enormous empirical studies have shown that male and female progeny in various species of arthropods (Li & Otvos 1999; Mahjoub et al . 2011), and undoubtedly other animal taxa (Coulson 1960; Mulvihill et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, early male emergence increases males mating opportunities (Bukowski & Avilés 2002). Apart from protandry, enormous empirical studies have shown that male and female progeny in various species of arthropods (Li & Otvos 1999;Mahjoub et al 2011), and undoubtedly other animal taxa (Coulson 1960;Mulvihill et al 1992;Fitze & Le Gillard 2008), suffer differently from environmental mortal agents such as natural enemies (Davis & Rendon-Salinas 2010;Mahjoub et al 2011), winter cold (Roth & Reinhardt 2003, changes in temperature (Goth & Booth 2004), habitat loss (Danks & Corbet 1973;Lounibos & Escher 2008), and food shortage (Hipkiss et al 2002). For example, populations of the tree-hole mosquitoes, Aedes triseriatus, A. sierrensis, and A. geniculatus in the southern USA have shown a significant male bias in some years.…”
Section: Figurementioning
confidence: 99%